PENGARUH PENDIDIKAN DAN PELATIHAN, SERTA UPAH TERHADAP PRESTASI KERJA KARYAWAN (Studi Kasus di PT. Bradjamusti Citra Nusantara Branch Office Riau) - M.A Baidowi (JURNAL KOMPETITIF, 2013)
Education and Training (Training), is an activity undertaken by the company to improve the quality of an employee's salary while remuneration for work performance provided by the employee. Thus it can be said that education and training and wages are those variables that can affect employees. Education and training programs in this study highlights how companies carry out these activities in preparation for the security personnel and the object of research is PT.Bradjamusti Citra Nusantara Branch Office Riau. The population is needed in this study were all securities PT. UPL (Unit of Field) Dumai Bradjamusti Nusantara Citra, totaling 166 people, the number of samples used as many as 62 people with the techniques of data collection conducted randomly through the distribution of questionnaires. Data analysis was performed using descriptive and inferential methods (correlation and regression) and hypothesis testing results performed by t test for partial correlation and multiple F test for correlation. The significance level was 95% (> 0.05).Ã‚Â Keywords : Education, Training and wagesÃ‚Â